Patient satisfaction with nurses' care is positively related to the nurse–patient relationship in Chinese hospitals: A multicentre study - Guo, Shujie; Chang, Yulan; Chang, Hongwei; He, Xiaoxiao; Zhang, Qiuxue; Song, Baoyun; Liu, Yilan (Frontiers in Public Health, 2023)
Background The nurse–patient relationship and nursing care satisfaction are important factors that represent whether patients experience the care they expect from nurses. However, research is lacking on the relationship between nursing staff and patients, and the correlation between nursing care satisfaction and relationship care in China. Therefore, this study aimed to explore the correlation between the nurse–patient relationship and patients' satisfaction with nursing care, to form a basis for corresponding intervention measures. Methods A total of 29,108 patients from 107 hospitals in 30 provinces/municipalities in China completed a general information questionnaire, the Nursing Care Satisfaction Scale, and Relational Care Scale. Results The average nurse–patient relational care scale score was 4.38 ± 0.57, and the average patients' satisfaction with nursing care scale score was 5.40 ± 0.86. Nursing care satisfaction score was significantly related to differences among patients in different age, gender, marital status, education level, occupation, residence, family per capita monthly income, type of medical insurance, medical department, and regional patient characteristics. The correlation analysis showed that the total nurse–patient relational care score and its three dimensions of caring, trust, and professional ethics correlated positively with nursing care satisfaction scores. The multiple linear regression analysis showed that patients' age, marital status, region, department, income, type of medical insurance and the caring, trust, and professional ethics dimensions of relational care predicted nursing care satisfaction. Conclusion Enhancing nurse–patient relational care improves nursing care satisfaction, reduces nurse–patient disputes, promotes early rehabilitation of patients, and ensures patient safety.